Synthesis and Characterization of Silver/Titanium dioxide Core-Shell Nanoparticles - Chin, Suk Fun; Pang, Suh Cem; Idely Dom, Freda Emmanuel (Borneo Journal of Resource Science and Technology, 2016)
Silver nanoparticles (AgNPs) with mean diameter of 150 nm were synthesized by using an aqueous-based reduction method. Ascorbic acid and sodium hydroxide (NaOH) were used as a reducing agent and as a catalyst, respectively. These AgNPs were subsequently coated with a layer of TiO2 to form Ag/TiO2 core-shell nanoparticles by using a sol-gel method. The particle sizes and morphology of Ag/TiO2 core-shell nanoparticles were characterized using scanning electron microscopy (SEM) and transition electron microscopy (TEM). The photocatalytic activity of the Ag/TiO2 core-shell nanoparticles were evaluated based on the degradation of methylene blue (MB) as the model reaction. The TiO2 coating has resulted in the enhanced photocatalytic activity of Ag nanoparticles as compared to bare Ag nanoparticles.